The Navajos : people of the Southwest - Bonvillain, Nancy (Brookfield, CT : Millbrook Press, 1995)
The history and culture of the Navajos, the largest Native American tribe in the United States today. The story of the Navajos is brought up to the present in this volume, and traditional songs and recipes are included.
Includes bibliographical references and index.
Keywords: Navajo Indians -- Juvenile literature; Navajo Indians; Indians of North America -- Southwest, New